Preparation, mechanical, dielectric and microwave absorption properties of hierarchical porous SiCnw-Si3N4 composite ceramics. Issue 9 (August 2022) - Yin, Shuang; Jiang, Yuhang; Su, Kai; Fang, Xia; Wang, Yang; Li, Quan; Yang, Jian
Abstract: Herein, hierarchical porous SiCnw -Si3 N4 composite ceramics with good electromagnetic absorption properties were prepared. A porous Si3 N4 matrix with different pore structures was first prepared by gelcasting-pressureless sintering (G-PLS) and gelcasting combined with particle stabilized foam-pressureless sintering (G-PSF-PLS). SiCnw was then introduced by catalytic chemical vapor deposition (CCVD). An increase in solid loading (25–40 vol%) decreased apparent porosity (47.7–41.3%) and improved flexural strength (142.19–240.36 MPa) and fracture toughness (2.25–3.68 MPa·m 1/2 ). The addition of foam stabilizer propyl gallate (PG, 0.5–1.0 wt%) significantly increased apparent porosity (73.2–86.4%) and realized large-sized spherical pores, reducing flexural strength (58.23–38.56 MPa) and fracture toughness (0.75–0.41 MPa·m 1/2 ). High apparent porosity and large-sized pores facilitated the introduction of SiCnw . The 25 vol% sample exhibited a reflection loss of − 14.67 dB with an effective absorption bandwidth of 3.47 GHz, suggesting a development potential in the electromagnetic wave absorption field.